1977
DOI: 10.1093/rheumatology/16.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing Spondylitis: Klebsiella and Hl-a B27

Abstract: A search for the presence of Klebsiella-Enterobacter spp. and Yersinia enterocolitica in urine and faeces of 63 patients with ankylosing spondylitis was conducted because these microorganisms have been demonstrated to cross-react immunologically with HL-A B27 positive lymphocytes. The patients were graded into three groups on the basis of disease activity. Klebsiella spp. were found in the faeces of 13 (93%) of the 14 patients with 'active' disease, 10 (48%) of the 21 patients with 'probably active' disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Nine serotypes were present for more than 14 days continuously; 24 serotypes were isolated on a single occasion only; 10 serotypes were isolated more than once but never on 2 consecutive occasions. On only 33 (Ebringer et al, 1977), suggesting a non-random difference in Klebsiella spp. in the 2 studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine serotypes were present for more than 14 days continuously; 24 serotypes were isolated on a single occasion only; 10 serotypes were isolated more than once but never on 2 consecutive occasions. On only 33 (Ebringer et al, 1977), suggesting a non-random difference in Klebsiella spp. in the 2 studies.…”
mentioning
confidence: 99%
“…The USA species Klebsiella pneumoniae (Edwards and Ewing, 1972) includes a wide variety of species biochemically subdivided in the UK into K. aerogenes, K. pneumoniae (sensu strictu), K. edwardsii, and K. atlantae (Cowan and Steel, 1965) and serologically contains some 75 capsular serotypes. A majority of the K. pneumoniae strains (Edwards and Ewing, 1972) implicated by Ebringer et al (1977) appear to be K. aerogenes. Klebsiella species are common agents in infections acquired in hospitals in the UK.…”
mentioning
confidence: 99%
“…Early studies by our group of 63 AS patients showed that K. pneumoniae was isolated more frequently during active phases of the disease [36]. In the second sequential study, of 163 AS patients, it was shown that clinical relapse was preceded by the appearance of K. pneumoniae in faecal samples [37] and active in¯am-matory disease was associated with elevation in total serum IgA, suggesting that a microbial agent was acting across a mucosal surface, such as the gut [38].…”
Section: Microbiological Studiesmentioning
confidence: 94%
“…The majority of enteric bacterial infections re sponsible for reactive arthritis confine to the exudative form of acute diarrheal disease [47], After invading the intestinal mucosa, the bacteria may stimulate the development of arthritis in one of two ways. First, by autoim mune mechanisms such as that described for ankylosing spondylitis and enteric Klebsiella infections [48], in which bacteria do not enter the joints but the inflammatory reactions evoked in joints are mediated through cross reaction mechanisms (true reactive arthritis). The other possibility is that microbial materi als in fact enter the joints and by themselves initiate an inflammatory reaction (postinfectious arthritis).…”
Section: Pathophysiological Aspects O F Reactive Arthritismentioning
confidence: 99%
“…[48]. According to these workers, pathological amounts of Klebsiella bacteria in the bowel supply the postulated environmental antigens necessary for the development of ankylosing spondyli tis.…”
Section: Ankylosing Spondylitis and The Gastrointestinal Tractmentioning
confidence: 99%